Determining the usefulness of systematic 18F-FDG PET/CT for the management of invasive fungal infection (PETIFI project): a prospective national multicentre cohort study protocol - Sonia García; Andrea Gutierrez; Isabel Gutiérrez; Elena Múñez; Begoña Rodríguez; Jorge Calderón-Parra; Karina Velasquez; Alejandro Callejas-Diaz; Antonio Ramos-Martinez; Ana Fernandez-Cruz (BMJ Open, 2023)
Introduction The evaluation of staging and activity of invasive fungal infection (IFI) is used to adjust the type and duration of antifungal therapy (AT). Typically anatomy-based imaging is used. Positron emission tomography/CT with 18F-fluorodeoxyglucose (18F-FDG PET/CT) not only evaluates more than one body area in one session, but adds functional information to the anatomic data provided by usual imaging techniques and can potentially improve staging of IFI and monitoring of the response to therapy. Our objective is to analyse the impact of the systematic use of 18F-FDG PET/CT in IFI diagnostic and therapeutic management.Methods and analysis Multicentre prospective cohort study of IFI with performance of systematic 18F-FDG PET/CT at diagnosis and follow-up that will be carried out in 14 Spanish tertiary hospitals. It is planned to include 224 patients with IFI over a 2-year study period. Findings and changes in management before and after 18F-FDG PET/CT will be compared. Additionally, the association of initial quantitative 18F-FDG PET/CT parameters with response to therapy will be evaluated.The primary endpoint is to compare the yield of 18F-FDG PET/CT with standard management without 18F-FDG PET/CT in IFI at initial assessment (staging) and in monitoring the response to treatment.The impact of the results of 18F-FDG PET/CT on the diagnostic-therapeutic management of patients with IFI (added value), as well as the prognostic ability of different quantification parameters of 18F-FDG PET/CT will be secondary endpoints.Ethics and dissemination The Clinical Research Ethics Committee of Puerta de Hierro-Majadahonda University Hospital approved the protocol of the study at the primary site. We plan to publish the results in high-impact journals.Trial registration number NCT05688592.